Mengintegrasikan Keberlanjutan, Strategi ESG, Etika Bisnis, dan Manajemen Perubahan di PT Blue Bird Tbk: Studi Kasus Tunggal Kualitatif - Budhi Santoso; Cynthia Amalia Gunawan; Eryca Dea Putri Ardiana Pratami; Januardi Darmawan; Valerie Richie (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2026)
This study investigates how PT Blue Bird Tbk integrates sustainability and ESG strategy into strategic management and organizational change in the Indonesian mobility industry. The study adopts a qualitative single-case study approach using secondary data, with Bluebird’s 2025 Annual and Sustainability Report as the primary empirical source. The paper also triangulates corporate disclosures with Indonesian sustainable finance regulations, national climate policy, sustainable mobility reports, business press, and recent academic literature. The theoretical lens combines the Resource-Based View, Stakeholder Theory, ESG integration, business ethics, circular economy, responsible artificial intelligence governance, and change management theory. The findings indicate that Bluebird’s sustainability strategy is increasingly embedded in competitive positioning through the BlueSky, BlueLife, and BlueCorps pillars, low emission fleet investments, digital service innovation, social programs, ethical governance, and risk-control structures. Nevertheless, the transition remains incomplete. The company’s emissions rose in 2025 as operations expanded, electric vehicles still represent a limited share of the fleet, independent assurance is not yet applied to sustainability data, and AI ethics and privacy preserving technologies are not yet disclosed as formal governance domains. The paper contributes to strategic management research by showing that sustainability leadership in emerging-market mobility firms depends on the integration of ESG metrics, circular practices, stakeholder legitimacy, digital governance, and change routines. Managerial implications emphasize a staged sustainability transformation roadmap, supplier ESG governance, carbon-neutrality targets, responsible AI principles, and cross-functional sustainability accountability.